Penghargaan pada Kerja Tangan dalam 1 Tesalonika 4:9-12 - Bonifasius Pradipta Putra Alam (Sekolah Tinggi Teologi Simpson Ungaran, 2022)
In his first letter to the Thessalonians, Paul wrote three main problems based on Timothy’s reports (1Thess 3:6). For the second problem, Paul discusses it with the technique of captatio benevolentiae. Paul first commended the Thessalonian way of life. For Paul, the Thessalonians had retained a distinctive Christian virtue, namely φιλαδελφία. Paul wrote the proof, “And indeed ye do it toward all the brethren which are in all Macedonia” (1Thess 4:10). Out of praise, Paul later turned his letter into exhortation. Paul asked the Thessalonians “to be quiet, and to do your own business, and to work with your own hands” (1Thess 4:11). By using social and lexical approaches in interpreting 1 Thess 4:9-12, the writer finds the main focus of the second problem. Paul actually wanted to direct his advice to few Thessalonians who were able to work but chose not to work and instead depended on others. Paul refers to them as ἀτάκτοι. For Paul, they had damaged the reputation of the church in the eyes of τοὺς ἔξω by being a parasite and a burden to the rest of the Thessalonians.